Extending the scope of proprietary remedies to recovery of pure profits from successful investment of bribes: the endgames in Lister v Stubbs - Hingun, Mohsin; Mohd. Sulaiman, Aiman @ Nariman (2015)
For more than a century Lister v Stubbs (1890) 45 Ch D 1 stood as authoritative Court of Appeal judgment denying the recovery of profits acquired from the successful investment of gains obtained in breach of fiduciary duties. The rule was rationalized on the basis that while the claimant was entitled to the proceeds so unlawfully obtained, he lacked any form of proprietary title to the profits accumulated by the defaulting fiduciary. The harsh reality of the rule produced an unfair outcome to the claimant and the Privy Council refused to apply it in Attorney-General for Hong Kong v Reid [1994] 1 AC 324. The rule also fell out of favour in other leading commonwealth jurisdictions and recently the English courts at all levels had the opportunity to reassess its relevance when the Supreme Court in FHR European Ventures LLP and others v Cedar Capital Partners LLC [2014] 4 All ER 79 consigned it to oblivion. The objective of this paper is to analyse the merits and the deficiencies of the rule and show how the judges of the English courts were prepared to act on policy ground, in comity with other common law jurisdictions in upholding justice in a borderless world.